969 ACUTE FRAILTY MODEL: A DISTRICT GENERAL HOSPITAL EXPERIENCE OF DELIVERING COMPREHENSIVE GERIATRIC ASSESSMENT. (14th June 2022) - Budihal, D; Andrews, S; Settle, S; Alexander, H; Haslam, S
Abstract: Introduction: Under the NHS Long Term Plan1, every hospital with a Type 1 Emergency Department (ED) has been asked to provide Acute Frailty Services for at least 70 hours a week. We have adopted a liaison model to ensure Comprehensive Geriatric Assessment at the front door. The Frailty Team now includes two Frailty Practitioners, a Specialist Registrar based in ED and the Acute Medical Unit (AMU) with Consultant Physician of the Week support. Method: The team attend multi-disciplinary meetings in ED and AMU on a daily basis. Frail patients are reviewed and Comprehensive Geriatric Assessments are undertaken together with appropriate signposting. The aim being, to enhance the care of frail patients at the earliest opportunity. Results: High bed utilisation comes at a cost and a longer length of stay (LOS) is associated with an increased risk of deconditioning. Since introducing incremental changes to our working model, the average LOS of patients on AMU has been reduced from a mean of 1.33 days to 0.82 days. This represents a 38.3% reduction from September 2020 to August 2021. This reduction has been sustained, while 30-day readmission rates have not increased. Feedback has been very positive from all the other teams involved. Conclusion: Our service has established a more positive working culture to efficiently manage frail patients. The AMU team now feel empowered to make patient-centric decisions regarding patient flow and discharges. Since this data was analysed we have implemented a further change to help enhance the care of frail patients. A list of appropriate patients is emailed to the hospital site team every afternoon to aid getting the right patients into the right beds. The impact of LOS on the frailty wards will then be reviewed following this introduction. Reference: 1. nhs-long-term-plan-june-2019.pdf (longtermplan.nhs.uk ).